Gerenciamento de Projetos no setor público: melhoria do Índice de Maturidade em Gestão no DNIT - LUANA CHRISTINA FARIAS NATIVIDADE (2023)
Project management proves to be a promising tool for successful outcomes in both public and private sectors. In the national context, its practice is less widespread in the realm of public infrastructure projects. A country's transportation infrastructure is directly linked to its competitiveness and economic growth. In Brazil, there is currently an emphasis on transitioning from a road-centric transportation system to railway and waterway systems, as evidenced by state programs such as "Pró-Trilhos" and "BR do Mar," respectively. Given the State's mission to provide transportation infrastructure and considering that the National Department of Transportation Infrastructure (DNIT) is the executing agency for such public policies at the federal level, this research aims to propose improvements to the maturity level of project management within the Aquatic Engineering Coordination of the Regional Superintendence of DNIT in the state of Mato Grosso do Sul. The maturity index research yielded a value of 2.64, indicating a "Known" level of project management practices. Subsequently, following the Prado-MMGP methodology, a Simplified Diagnosis of the maturity situation was obtained, evaluating sector weaknesses, identifying their causes, and suggesting possible countermeasures. It was generally observed that the main weaknesses of the sector are associated with the absence of guidelines, support, or institutional incentives related to the theme. Documentary research conducted within the Electronic Information System - SEI/DNIT, between the years 2014 and 2023, revealed that the Autarchy has been undertaking actions to improve project management since 2014. However, these measures were primarily focused on the DNIT Headquarters and were either discontinued or inadequately integrated within the institution. Expert opinions reinforce the inference that there are scattered management practices that are beneficial to the Department but are still underutilized and not widely disseminated. The stages completed in this research allowed the formulation of a Maturity Growth Plan for project management within the Aquatic Engineering Coordination of SR/MS, with the goal of achieving a 2.86 index within 24 months. The detailed plan is outlined in this work. Keywords: Project management. Project Management Maturity. Public Sector. DNIT. Government. Infrastructure.